Clinical management of dietary induced urolithiasis associated with balanoposthitis in a Boer goat - Abba, Y.; Abdullah, Faez Firdaus Jesse; Abu Daud, Nur Hardy; Shaari, R.; TijjanI, A.; Sadiq, M. A.; Mohammed, Konto; Adamu, Lawan; Mohd, A. M. L. (Al Fateh University,University of Tripoli, 2015)
A Boer-Kajang cross male goat was presented to the Veterinary Hospital, University Malaysia Kelantan with a history of dysuria, hematuria and restlessness. The goat was intensively managed (confined to the pen) and fed with only palm kernel cake for the last three months. Physical examination revealed that the goat was dull, depressed, having an inflamed penis and prepuce with blood stained urine dripping from the penis. The differential diagnoses were obstructive urolithiasis, urinary tract infection and balanoposthitis. Based on the history, clinical signs, physical examination, urinalysis, ultrasonagraphy and feed analysis, the goat was diagnosed with obstructive urolithiasis and balanoposthitis. Treatment was instituted by amputation of the urethral process and retrograde urohydropulsion to relieve the blockade. Sulfadiazine-trimethoprim (Norodine®24) 15mg/kg, I.M; flunixin meglumine 2.2mg/kg, I.M; vitamin B complex 1ml/10kg, I.M and ammonium chloride 300mg/kg orally were administered. The goat responded well to treatment and was recovering well during a follow up visit.